The More, the Better: The Use of Multiple Landmark Configurations to Solve the Phylogenetic Relationships in Musteloids - Catalano, Santiago Andres (2015)
Although the use of landmark data to study shape changes along a phylogenetic tree has become a common practice in evolutionary studies, the role of this sort of data for the inference of phylogenetic relationships remains under debate. Theoretical issues aside, the very existence of historical information in landmark data has been challenged, since phylogenetic analyses have often shown little congruence with alternative sources of evidence. However, most analyses conducted in the past were based upon a single landmark configuration, leaving it unsettled whether the incorporation of multiple configurations may improve the rather poor performance of this data source in most previous phylogenetic analyses. In the present study, we present a phylogenetic analysis of landmark data that combines information derived from several skeletal structures to derive a phylogenetic tree for musteloids. The analysis includes nine configurations representing different skeletal structures for 24 species. The resulting tree presents several notable concordances with phylogenetic hypotheses derived from molecular data. In particular, Mephitidae, Procyonidae, and Lutrinae plus the genera Martes, Mustela, Galictis, and Procyon were retrieved as monophyletic. In addition, other groupings were in agreement with molecular phylogenies or presented only minor discordances. Complementary analyses have also indicated that the results improve substantially when an increasing number of landmark configurations are included in the analysis. The results presented here thus highlight the importance of combining information from multiple structures to derive phylogenetic hypotheses from landmark data.